2018
DOI: 10.24193/ojmne.2018.27.04
|View full text |Cite
|
Sign up to set email alerts
|

Study Regarding Romanian Students’ Perception and Behaviour Concerning the Fintech Area with a Focus on Cryptocurrencies and Online Payments

Abstract: Fintech, which is a shorthand expression for financial technology, is basically referring to all the technological innovations in the financial sector that started to develop exponentially, especially in the second decade of the 21st century, in the era of the mobile internet revolution. The Generation Z, also called Gen Tech, who was growing up using the internet and especially the mobile internet on a daily basis, will probably be the larger adopter and beneficiary of these innovative financial technologies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Cryptocurrency is the first one of the many applications built by using blockchain technology. This technology provides the necessary rigorous regulatory frameworks to the newly emerged type of currency, i.e., cryptocurrency, by incorporating innovative vital principles such as cryptography, public distribution of contents through public ledgers, and decentralization [1].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptocurrency is the first one of the many applications built by using blockchain technology. This technology provides the necessary rigorous regulatory frameworks to the newly emerged type of currency, i.e., cryptocurrency, by incorporating innovative vital principles such as cryptography, public distribution of contents through public ledgers, and decentralization [1].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the current global and economic context, blockchain technology has revolutionized individual interactions and financial operations such as investment, trading, and online payments. Moreover, this blockchain also fulfills the requirements of a demanding regulatory tool for a newly emerged category of currency, i.e., virtual currency to regulate it securely through decentralization, cryptography, and public circulation of its content [1]. It works like a computer that is connected to a whole network of users and has a copy of all transactions made by the users (Sudzina & Pavlicek, [2]).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the authors' research (March 2021) of Scopus, a citation database, only four articles were found concerning the searched term {("Generation Z" OR "Generation Y" OR "young generations") AND (cryptocurrency OR bitcoin)} in any of the records. Regrettably, only one of them directly concerned generation research [12]. Other articles only concern subsidiary research mentioning younger generations (see [13][14][15]).…”
Section: Introductionmentioning
confidence: 99%
“…They show that acceptance of FinTech services remains low because people who are strongly interested in controlling their own data feel uneasy about protection of personal information when using FinTech technologies. On the other hand, Duma and Gligor (2018) surveyed the 'digital native' generation (Generation Z) regarding online transactions and acceptance of virtual currencies/blockchains, and found that this generation, regardless of the complex technology underlying FinTech services, enjoys the freedom, mobility, coolness, and nimbleness that FinTech brings, and accepts innovation and continuous technological development very naturally. Pousttchi and Dehnert (2018) used a grounded theory approach to investigate the impact of digitisation on consumer decision-making in retail banking; they argue that, in order to compete with FinTech companies, existing financial institutions must use a data-driven approach that enables them to provide services to the right customers in the right way and at the right time.…”
Section: Research On Society's Acceptance Of New Value-addedmentioning
confidence: 99%